2020
DOI: 10.1177/1535759720973987
|View full text |Cite
|
Sign up to set email alerts
|

Continuous EEG in ICU: Not a Luxury After All

Abstract: [Box: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…34 However, various concerns have been raised, such as choice of endpoint, ability to convert to cEEG upon seizure/status epilepticus detection, delayed time to EEG start, and active cEEG monitoring during business hours only, which may explain a lower rate of cEEG intervention. 35,36,37 While evidence emerges about what and in whom constitutes an acceptable “seizure miss rate,” our findings suggest that non-cEEG models of practice can face median false-negative rates as high as missing one in five seizures. Although the 2HELPS2B criteria imply that low-risk EEGs can safely stop running at 1 hour, approximately 3/4 of our recordings were medium or high risk, but median duration of all recordings was only just over 1 hour.…”
Section: Discussionmentioning
confidence: 69%
“…34 However, various concerns have been raised, such as choice of endpoint, ability to convert to cEEG upon seizure/status epilepticus detection, delayed time to EEG start, and active cEEG monitoring during business hours only, which may explain a lower rate of cEEG intervention. 35,36,37 While evidence emerges about what and in whom constitutes an acceptable “seizure miss rate,” our findings suggest that non-cEEG models of practice can face median false-negative rates as high as missing one in five seizures. Although the 2HELPS2B criteria imply that low-risk EEGs can safely stop running at 1 hour, approximately 3/4 of our recordings were medium or high risk, but median duration of all recordings was only just over 1 hour.…”
Section: Discussionmentioning
confidence: 69%
“…In line with the few previous studies on this topic, the results of the present analysis suggest that rEEG seems feasible as a neurophysiological biomarker and NCU monitoring option for 12-month survival in adult HE patients [ 21 , 48 ]. Considering the still-limited availability of cEEG in rural regions and developing countries, rEEG is a viable alternative to the gold standard of neurophysiological monitoring in neurocritical care [ 19 ]. A recent international survey showed that only a few ICUs have 24/7 availability of EEG technicians and specialized physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the availability of cEEG is usually limited to maximum care providers or large specialized hospitals and is not comprehensively accessible, especially in rural areas and developing countries [ 19 ]. In addition, extraordinary medical circumstances, such as the recent SARS-CoV-2 pandemic, can significantly restrict the availability of cEEG at neurocritical care centers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%